Anemia and associated factors among school children in Makkah province, Saudi Arabia - Omar M., Altalhi Roaa (2016)
Anemia among children is considered as moderate public health problem in Saudi Arabia and among the most important public health problems around the world. This cross sectional study aimed to determine the prevalence of anemia and its associated factors among 7 to 9 years old schoolchildren in Makkah province of Saudi Arabia. A questionnaire was utilised to assess the socio demographic characteristics, body weight status, food security status, dietary intake and hemoglobin level of the respondents. Weight and height of the respondents were measured and body mass index (BMI) was computed to assess the body weight status. The food security status was assessed using a 10-item questionnaire by Radimer/Cornell Hunger and food insecurity. The dietary intake was assessed using two days 24-hour dietary recall by the parents /guardian of the respondents. The dietary intakes data were analysed using Nutritionist Pro software and the mean intakes of the macro and micronutrients were compared with Dietary Reference Intake (DRI). The Hemoglobin level (Hb) was measured by automated hematology counters method. Five-ml of venipuncture blood were drawn by a trained nurse. The cut-off point for Hb<11.5 g/l was diagnose anemia. Body weight status was assessed using Anthroplus software v1.0.4 to determine BMI for age. A total of 240 primary schools students with equal distribution of boys and girls were recruited through multi stage cluster sampling. The mean age (±SD) of the respondents was 7.98 ±0.80 years. More than half mean (54.2 %) of the respondents had families with monthly household income more than the average (> 13106 SAR). Majority of the respondents (87.9%) had 2 to 4 siblings. Furthermore, more than half of the respondent's fathers (52.1%) and mothers (55.0%) had education at tertiary level. Majority of the respondents (88.3%) had household size between four to six people. Mean for body weight, height and BMI were; 24.75 ±6.95 kg, 1.19 ±0.08 m and 17.17±3.24 kgm-2 respectively. Majority of the respondents (67.1%) were classified as normal, 16.7% overweight, 13.3% obese and only 2.9% thinness. The mean for total energy, carbohydrate, fat and protein intake were 1239±193 kcal, 181.09 ± 26.42g, 38.05 ± 8.88g, 40.78 ± 6.10g respectively. The determined mean for vitamin B12, vitamin B6, vitamin A, iron, folic acid and calcium of all the respondents were 2.09 ± 0.72mg, 0.86 ± 0.23 mg, 206.16 ± 67.41mg, 9.81 ± 2.36 mg, 279.13 ± 72.82 mg, 571.25 ± 149.29 mg respectively. The prevalence of anemia was 18% for all respondents with higher prevalence noted among girls (20.8%) as compared to boys (15.0%). A significant association was observed between anemia with vitamin B12, folic acid and protein. Most of the households (97.5%) were considered food-secured. There was significant difference (t=2.608, p<0.05) in the mean value of Hb level between boys (12.56 ± 1.05 g/l) and girls (12.23 ± 0.91 g/l). Using Binary Logistic Regressions Test, there were significant relationships (p<0.05) between vitamin B12 (OR=0.45, 95% CI: 0.26-0.78), folic acid (OR=0.99, 95%CI: 0.98-0.99) and protein intake (OR=1.09, 95%CI: 1.03-1.16) with anemia. Logistic regressions model for anemia status indicated that intake of vitamin B12, folic acid and protein were the significant determinants of anemia status. High prevalence of anemia among school children in Saudi Arabia requires great attention from related authorities. Thus, implicates for a proactive planning for preventive measures and implementation of intervention program on nutrition and health that emphasise on the dietary intakes.